The Role of Labour Inspector in Preventing and Overcoming Child Labour Exploitation: A Critical Review - Prawira, M. Rizki Yudha; Muhammad Raihan Yulistio (Veteran Law Review, 2024)
The right to decent work is a fundamental human right that applies to everyone without exception, including children. This is clearly stated in several Indonesian laws, such as Law No. 39 of 1999 concerning Human Rights, Law No. 13 of 2003 concerning Manpower, and Law No. 23 of 2002 in conjunction with Law No. 35 of 2014 concerning Children. Although many legal provisions aim to protect children from exploitation in the workplace, the situation still needs improvement due to a lack of effective implementation. The labour inspectorate is responsible for enforcing these laws, but the number of inspectors is limited, and their authority often needs to be fully implemented. As a result, many children are still working in dangerous or exploitative conditions, which is unacceptable. Therefore, it is crucial to strengthen the labour inspectorate's role by increasing the number of implementing personnel and improving their authority's effectiveness to ensure child labours’ protection.